Synthesis of Monobactams via the Diastereoselective Kinugasa Reaction - Kabala, Kamil; Grzeszczyk, Barbara; Furman, Bartłomiej; Chmielewski, Marek; Solecka, Jolanta; Guśpiel, Adam (Synthesis, 2018)
The Kinugasa reaction between phthalimidoacetylene and cyclic nitrones derived from l-phenylglycine or l-serine and glyoxylic acid, catalyzed by copper(I) chloride in the presence of triethylamine, is reported. The acetylene molecule approaches the nitrone exclusively anti to the bulky substituent next to the nitrogen atom to provide the cis-substituted β-lactam ring preferentially. The six-membered oxazinone ring can be easily opened, the phthaloyl residue can be transformed into a Boc protecting group, and substituents at the C-4 carbon atom and the nitrogen atom of the β-lactam ring can be easily removed or transformed into groups suitable for further synthesis of a variety of monobactam structures. Selected synthesized compounds were evaluated for their biological activity, showing interesting properties.
Keywords: β-lactams; monobactams; Kinugasa reaction; copper catalysis; nitrones